Reconstruction of Integrative Character Education: A Comparative Analysis of the Thought of Imam Al-Ghazali and Thomas Lickona in Contemporary Moral Crisis - Ahmad Fathi Naufal Hasby; Habibah Afiyanti Putri; M. Arif Hidayatulloh (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the concept of character education according to Imam Al-Ghazali and Thomas Lickona and examine the relevance of the integration of the two ideas in contemporary Islamic education. This research uses a qualitative approach with the library research method. Data was obtained from books, scientific journals, and various relevant academic publications. The data analysis technique was carried out through content analysis and comparative analysis to find similarities, differences, and forms of integration of the concept of character education of the two characters. The results of the study show that Imam Al-Ghazali emphasized character education through the formation of morals, purification of the soul, self-control, habituation, and example based on Islamic spiritual values. Meanwhile, Thomas Lickona emphasized character education through the development of moral knowing, moral feeling, and moral action systematically to form moral awareness and social responsibility of students. Despite having different foundations of thought, the two characters have the same goal, which is to form human beings with morals and good character. This study concludes that the integration of Al-Ghazali and Thomas Lickona's thinking can be a more comprehensive and relevant model of character education in dealing with moral crises in the digital era. The implications of this study show that character education needs to be applied holistically through synergy between schools, families, and the social environment in order to form students who have strong moral integrity, spirituality, and social responsibility.